Integrating problem-based learning with schoology in criminal law course - Rachman, Dzul; Pratama, Rio Arif; Mahayanti, Ni Wayan Surya; Kusuma, I Putu Indra (Psychology, Evaluation, and Technology in Educational Research, 2020)
This study indents to investigate students’ perception of problem-solving skill and influence of Schoology on students’ ability to solve problems used in the criminal course in tertiary education. In reality, this course requires many activities involving students to solve various types of cases. This study used the quasi-experimental method at the class of criminal law. The students were from the Faculty of Law taking a 14 week enrolled in the Criminal course in the second semester. The instruments in this study were test and questionnaire. Data were analyzed using descriptive and inferential analysis. The overall, There are significant differences in problem-solving skills between the students who learn the material of solubility and constant solubility product using Problem-solving learning model through Schoology in the learning activities. Furthermore, this learning model can also be applied to overcome the lack of time allocation for face-to-face learning.